P.101: Investigation on Flexoelectric Effect in the Fringe Field Switching Mode. Issue 1 (1st July 2013) - Jeong, Il Hwa; Jang, In Won; Kim, Dae Hyoung; Han, Ji Su; Kumar, Baliyan Vijay; Lee, Seung Hee; Ahn, Seon Hong; Cho, Sung Ho; Yi, Chung
Abstract Orientation of liquid crystal (LC) in an on state of the fringe field switching (FFS) mode has splay and bend deformation of LC director, which might cause spontaneous polarization by LC layer itself. Existence of flexoelectric effect is confirmed by observing appearance of flickering while the device is driven by ac voltage. We have tested LC mixtures having positive dielectric anisotropy and studied flexoelectric effects dependent on frequency and temperature.